Antiviral activity of high pressure processing of Korean fermented clam jeotgal against human norovirus GII.4 infectivity - Jeon, Eun Bi; Jeong, Heon Sang; Park, Shin Young (Frontiers in Sustainable Food Systems, 2024)
Human norovirus can accumulate in shellfish in contaminated waters through their filter-feeding mechanism, and they can retain the virus for extended periods. It is important to note that this bioaccumulation can pose a risk to human health if the shellfish are consumed raw or undercooked. Jeotgal is a salted fermented food made from various types of seafood and is consumed in Korea and certain Asian countries. However, jeotgal is not sterilized during preparation and is typically consumed raw after fermentation. Bivalve shellfish, such as oysters, mussels, and clams, are considered high-risk foods for HuNoV transmission due to the potential for contaminated water to lead to the accumulation of HuNoV in their digestive tissues. Other foods may also contribute to HuNoV transmission, but bivalve shellfish are particularly susceptible. This study investigated the effect of high pressure processing (HPP) on the inactivation of HuNoV GII.4, in clam jeotgal. After HPP treatment, HuNoV GII.4 was quantified using RT-qPCR and combined with Propidium monoazide (PMA) + Sarkosyl, a pre-treatment agent, before RT-qPCR. As a result of this treatment HuNoV GII.4 was significantly (p < 0.05) reduced to 0.27–1.38 log copy number/μL. Compared to the RT-qPCR, the reduction in HuNoV was significantly greater (p < 0.05) (0.24 log, 43%) log copy number/μL in PMA + Sarkosyl/RT-qPCR when clam jeotgal was treated at 200–600 MPa of HPP. The Hunter “L” and “a” and Hunter “b” values increased and decreased significantly (p < 0.05), respectively, as the pressure of the HPP increased. Although the sensorial color significantly (p < 0.05) decreased as the pressure of the HPP increased, most of the sensory parameters (smell, taste, appearance, and overall acceptability) and the pH were not significantly (p < 0.05) different between non-HPP treated and HPP treated samples. Therefore, HPP pressure in excess of 400 MPa for 5 min appeared to be effective to viably reduce HuNoV levels by ≥90% without significant changes in the overall quality (pH, and most sensory parameters) of clam jeotgal.